A sustainable route for the recovery of metals from waste printed circuit boards using methanesulfonic acid. (1st June 2023) - Jadhao, Prashant Ram; Mishra, Snigdha; Singh, Aditya; Pant, K.K.; Nigam, K.D.P.
Abstract: The rapid increase in electronic waste (e-waste) generation and its unsustainable management pose a threat to the environment and human well-being. However, various valuable metals are present in e-waste, which makes it a potential secondary source to recover metals. Therefore, in the present study, efforts were made to recover valuable metals (Cu, Zn, and Ni) from waste printed circuit boards (WPCB) of computers using methanesulfonic acid (MSA). MSA is contemplated as a biodegradable green solvent and has a high solubility for various metals. The effect of various process parameters (MSA concentration, H2 O2 concentration, stirring speed, liquid to solid ratio, time, and temperature) was investigated on metal extraction to optimize the process. At the optimized process conditions, 100% extraction of Cu and Zn was achieved, while Ni extraction was around 90%. The kinetic study for metal extraction was performed using a shrinking core model and findings showed that MSA-aided metal extraction is a diffusion-controlled process. Activation energies were found to be 9.35, 10.89, and 18.86 kJ/mol for Cu, Zn, and Ni extraction, respectively. Furthermore, the individual recovery of Cu and Zn was achieved using the combination of cementation and electrowinning, which resulted in 99.9% purity of Cu and Zn. The current study proposes a sustainable solution for the selective recovery of Cu and Zn from WPCB. Graphical abstract: Image 1 Highlights: Biodegradable green solvent (methanesulfonic acid) was used for metal recovery. 100% extraction of Cu and Zn was achieved while the extraction of Ni was 90%. Combination of cementation and electrowinning was employed for metal recovery. Individual recovery of Cu and Zn was achieved with 99.9% purity. Metal extraction using MSA is a diffusion-controlled process.